US-Elastography for Breast Lesion Characterization: Prospective Comparison of US BIRADS, Strain Elastography and Shear wave Elastography - Cantisani, Vito; David, Emanuele; Barr, Richard G.; Radzina, Maija; de Soccio, Valeria; Elia, Daniela; De Felice, Carlo; Pediconi, Federica; Gigli, Silvia; Occhiato, Rossella; Messineo, Daniela; Fresilli, Daniele; Ballesio, Laura; D'Ambrosio, Ferdinando (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To evaluate the diagnostic performance of strain elastography (SE) and 2 D shear wave elastography (SWE) and SE/SWE combination in comparison with conventional multiparametric ultrasound (US) with respect to improving BI-RADS classification results and differentiating benign and malignant breast lesions using a qualitative and quantitative assessment.Materials and Methods In this prospective study, 130 histologically proven breast masses were evaluated with baseline US, color Doppler ultrasound (CDUS), SE and SWE (Toshiba Aplio 500 with a 7–15 MHz wide-band linear transducer). Each lesion was classified according to the BIRADS lexicon by evaluating the size, the B-mode and color Doppler features, the SE qualitative (point color scale) and SE semi-quantitative (strain ratio) methods, and quantitative SWE. Histological results were compared with BIRADS, strain ratio (SR) and shear wave elastography (SWE) all performed by one investigator blinded to the clinical examination and mammographic results at the time of the US examination. The area under the ROC curve (AUC) was calculated to evaluate the diagnostic performance of B-mode US, SE, SWE, and their combination.Results Histological examination revealed 47 benign and 83 malignant breast lesions. The accuracy of SR was statistically significantly higher than SWE (sensitivity, specificity and AUC were 89.2 %, 76.6 % and 0.83 for SR and 72.3 %, 66.0 % and 0.69 for SWE, respectively, p = 0.003) but not higher than B-mode US (B-mode US sensitivity, specificity and AUC were 85.5 %, 78.8 %, 0.821, respectively, p = 1.000).Conclusion Our experience suggests that conventional US in combination with both SE and SWE is a valid tool that can be useful in the clinical setting, can improve BIRADS category assessment and may help in the differentiation of benign from malignant breast lesions, with SE having higher accuracy than SWE.
Keywords: breast lesions; characterization; shear wave elastography; strain elastography; BIRADS